2016
DOI: 10.1038/srep37864
|View full text |Cite
|
Sign up to set email alerts
|

Soil respiration and its environmental response varies by day/night and by growing/dormant season in a subalpine forest

Abstract: Comparisons of soil respiration (RS) and its components of heterotrophic (RH) and rhizospheric (RR) respiration during daytime and nighttime, growing (GS) and dormant season (DS), have not being well studied and documented. In this study, we compared RS, RH, RR, and their responses to soil temperature (T5) and moisture (θ5) in daytime vs. nighttime and GS vs. DS in a subalpine forest in 2011. In GS, nighttime RS and RH rates were 30.5 ± 4.4% (mean ± SE) and 30.2 ± 6.5% lower than in daytime, while in DS, they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 59 publications
1
9
2
Order By: Relevance
“…The higher Rs day than Rs night in autumn corroborates similar findings in a seasonal dry temperate rainforest (Jassal et al, 2007), a longleaf pine wiregrass savanna (Ford et al, 2012) and a subalpine forest (Hu et al, 2016). In addition to the stimulation of higher temperatures in daylight on microbial activity and photosynthesis rate (Carey et al, 2016;Ford et al, 2012;Shi et al, 2006), another possible reason is that the proportion of litter-associated respiration to total Rs in autumn increases owing to the light dependency of the litter component (Zimmermann et al, 2009) and contributes to higher soil CO 2 flux during daytime than during nighttime.…”
Section: Higher Rs Night Than Rs Day In Spring and Summer Challenges ...supporting
confidence: 86%
See 3 more Smart Citations
“…The higher Rs day than Rs night in autumn corroborates similar findings in a seasonal dry temperate rainforest (Jassal et al, 2007), a longleaf pine wiregrass savanna (Ford et al, 2012) and a subalpine forest (Hu et al, 2016). In addition to the stimulation of higher temperatures in daylight on microbial activity and photosynthesis rate (Carey et al, 2016;Ford et al, 2012;Shi et al, 2006), another possible reason is that the proportion of litter-associated respiration to total Rs in autumn increases owing to the light dependency of the litter component (Zimmermann et al, 2009) and contributes to higher soil CO 2 flux during daytime than during nighttime.…”
Section: Higher Rs Night Than Rs Day In Spring and Summer Challenges ...supporting
confidence: 86%
“…Different from other studies utilizing a fixed timeslot to classify day and night throughout the year, for example, 7 am to 6 pm as daytime and 7 pm to 6 am as nighttime (Gómez-Gener et al, 2021;Gutiérrez del Arroyo & Wood, 2020;Hu et al, 2016), we used photosynthetically active radiation (PAR; 50Y; Vaisala, Helsinki, acquired above the canopy near the top of the tower) to classify the daytime (PAR >0 μmol m −2 s −1 ) and nighttime (PAR = 0) periods (Yang et al, 2009), which could minimize uncertainty and bias in estimating Rs day and Rs night .…”
Section: Statistical Analysesmentioning
confidence: 98%
See 2 more Smart Citations
“…We leveraged a pre‐existing soil respiration database (SRDB version 5, Jian et al., 2021) and filtered for studies that manipulated precipitation (increase, decrease, or both) and reported at least one of the following for both treatment and control field plots: (a) annual soil respiration, (b) mean growing season soil respiration, or (c) annual soil heterotrophic flux. Although the proportion of annual respiration that growing season respiration comprises varies by ecosystem (Brooks et al., 2005; Hu et al., 2016), the mechanisms underlying responses to precipitation change are the same. Additionally, despite heterotrophic measurements lacking plant root respiration, this flux often represents more than 50% of soil respiration (Jian et al., 2022).…”
Section: Methodsmentioning
confidence: 99%